Strongyloidiasis in the immunocompetent: an overlooked infection - Niranjan Tachamo; Salik Nazir; Saroj Lohani; Paras Karmacharya (Greater Baltimore Medical Center, 2016)
Strongyloidiasis is a parasitic infestation caused by Strongyloides stercoralis. Most cases are asymptomatic; however, symptomatic patients may present with a wide range of non-specific cutaneous, pulmonary, or gastrointestinal symptoms posing a diagnostic dilemma and delay in diagnosis. We report a case of a 58-year-old female who presented with months of generalized pruritus and abdominal discomfort along with persistent eosinophilia due to strongyloidiasis, which completely resolved with treatment.